Mixed Ligand Complexes of Silver(I) Metal Chelates of Some Organic Acids With Derivatives of 5,7-Dinitro-oxine - KUMAR, BIRENDRA; SHEKHAR GUPTA, BALENDU; RANJAN PANDEY, RAJESH; KUMAR SINGH, RATNESH (Asian Journal of Chemistry, 2010)
A series of some mixed ligand silver(I) complexes having the general formula ML.HL', where M = Ag(I), L = deprotonated o-nitrophenol, 2,4-dinitrophenol, 2,4,6-trinitrophenol, 8-hydroxyquinoline(oxine), o-aminobenzoic acid, salicylic acid or acetylsalicylic acid, HL' = 5,7- dinitro-oxine have been synthesized. The structure of these complexes were confirmed by analytical and spectral data.